Endoscopic cyclophotocoagulation for glaucoma compared to alternative procedures –A Systematic review - Tariq Alasbali (Oman Journal of Ophthalmology, 2023)
INTRODUCTION: Despite many recent developments, preference in the choice of surgical treatment of uncontrolled intraocular pressure (IOP) remains a challenge. OBJECTIVE: This study compares the clinical efficacy and safety of endoscopic cyclophotocoagulation (ECP) to alternative surgical procedures, for all types of glaucoma. METHODOLOGY: The methodology adheres to the preferred reporting items for systematic reviews and meta-analyses guidelines for systematic review reporting. Studies reporting ECP and alternative surgeries in treating refractory glaucoma, neovascular glaucoma, aphakic glaucoma, filtering surgical failure-induced glaucoma, congenital or juvenile glaucoma, and secondary glaucoma such as uveitis glaucoma, traumatic glaucoma, secondary glaucoma postcorneal transplantation, etc. were included. The efficacy was evaluated from the number of IOP-lowering drugs, and mean change in pre- and post-IOP were the outcomes assessed in ECP and non-ECP groups in this review. Evaluations of the postoperative complications revealed the safety assessment of the procedure. RESULTS: In total, 11 relevant studies were selected in this study with a total of 5418 eyes, including 763 eyes in the ECP group and 4655 in the non-ECP group. This review observed that both ECP and non-ECP procedures had been successful in reducing postoperative IOP. CONCLUSION: It can be deduced from this review, that all types of glaucoma can be treated efficiently with significantly higher success rates with ECP and ECP demonstrates lowest postoperative complications when compared to non ECP procedures. This review provides updated scientific evidence which caters to support clinical decisions for surgical treatment of glaucoma.